Economic means of the support cycle transport and possibilities of financing for the cycling - Vohnická, Pavla (Univerzita Pardubice, 2010)
Motor transport brings in the community the succession of the adverse effects as the externalities consequently it is undesirable to ignore the contemporary trend of uncontrolled motor transport increase but it is demanded to give support to all possibilities which bring on the contrary sustainable growth of the motor transport, also belonging to the cycle transport support. In present time there is the modern trend in this domain the build-up and extend the quality safety and functional cycle paths and routes which should contribute to support at the progressive cycle transport intensity increase. The evident key question of the next cycle transport development is sufficient financial means for the build-up of cycle paths and cycle routes. Classical home sources are public and regional budgets though limited and mostly are not managing financing all costs. But they are acceptable as one of several financial services. The most notable home source is the State Fund for Transport Infrastructure which provides a year considerable finance means for the build-up of cycle paths and cycle routes. In 2009 SFTI budget proposition is set 180 million crowns aside for these purposes the contribution can be provided for project up to 65% of relevant costs. The rules make it possible to co financing the projects which have received grants from EU Structural Funds. The foreign source is first of all EU Structural Funds. In actual period 2007 – 2013 are Regional Operational Programs acceptable. They are based on the statistical units NUTS II which are situated in the Czech Republic with the exception of the capital city Praha. They are Moravskoslezsko, Střední morava, Střední Čechy, Jihovýchod, Severovýchod Severozápad and Jihozápad. An applicant gives request for a grant in terms of the competent ROP who is belonging to the respective one. Every ROP offers another level of financial means University of Pardubice, Jan Perner Transport Fakulty which are classified into Priority Axes. Alike as in last period there are set similar conditions of the grant namely that of these ROP there can be financing maximum 85% of relevant costs. Except for the financial scope the cycle support can be even a layout cycle paths and cycle routes at railway bodies after cancelled railway´s tracks whose parameters are similar as cycle paths or (if you like) routes parameters and then the reconstruction of railway body is not so financially demanding. Next possibility is to build-up cycle paths and cycle routes along water streams, but the build-up can be made as roads for more categories of transport because the roads are used even for the River-Basins vehicles. The legislative possibility for cycle support is so–called Landed Estate Modifications which solve even strained legal relations of the landholders over which a layout cycle paths and cycle routes is planned. The aim of the article is to demonstrate the support means for build-up of cycle paths and cycle routes.
Keywords: Regional Operational Programme; EU Structural Funds; the State Fund for Transport Infrastructure; cycle path; cycle route; railway body